Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Water Use in Rice Crop Cultivation in India: A Quantitative Assessment - Manish Debnath; Sumanta Chatterjee; A. K. Nayak; D. Chakraborty; H. Pathak (Agricultural Research, 2026)

Targeting west nile virus replication by xanthine inhibitors - Theresa H. Nguyen; Jessica L. Smith; Shuklendu D. Karyakarte; John P. Tillotson; Sarath C. Sarngadharan; Fuad Al Abir; Jake Y. Chen; Sixue Zhang; Lynn Rasmussen; Robert Bostwick; Alec J. Hirsch; Corinne E. Augelli-Szafran; et al. (Medicinal Chemistry Research, 2025)

A novel tamoxifen-inducible Mct8-CreERT2 mouse model for targeted studies of Mct8-expressing cells and thyroid hormone transport and function - Anna Molenaar; Noémi Mallet; Marin Bralo; Luciano J. Hoeher; Sonja C. Schriever; Ekta Pathak; Miriam Bernecker; Timo D. Müller; Ali Ertürk; Alberto Cebrian-Serrano; Paul T. Pfluger (Transgenic Research, 2025)
Deficiency of the Monocarboxylate Transporter 8 (MCT8) severely impairs thyroid hormone (TH) transport into the brain, disrupting brain development as well as peripheral TH homeostasis. Studies assessing MCT8 expression patterns and tissue-specific pathologies induced by local TH-deficiency are often inconclusive due to unreliable antibody staining and the lack of functional tools to specifically target MCT8-expressing cells. For this purpose, we generated non-inducible Mct8-Cre and tamoxifen-inducible Mct8-CreERT2 mice. Mct8-Cre;Sun1-sfGFP mice demonstrated ubiquitous Sun1-sfGFP expression, due to early recombination driven by Mct8 gene expression at the stage of trophoblast implantation. Tamoxifen injection in 6-week-old Mct8-CreERT2 mice induced reporter expression specifically in Mct8-expressing cells in the brain and peripherally in liver, kidney, and thyroid, without leaky reporter expression in vehicle controls. Using vDISCO tissue clearing and 3D-imaging of GFP-nanobody-boosted mice, we further identified the sublingual salivary gland and the prostate as prominent Mct8-expressing organs. Nuclei from Mct8-expressing cells in the brain could selectively be enriched using fluorescence-activated nuclei sorting on Mct8-CreERT2;Sun1-sfGFP mice and characterized as choroid plexus cells and tanycytes. Our new inducible Mct8-CreERT2 line provides researchers with a tool to reliably mark, enrich, and characterize Mct8-expressing cells and to genetically modify genes specifically in these cells to study thyroid hormone transport and function.

Climate Resilient Crop Varieties: Mainstreaming to Improve Yield and Moderate Farmers’ Risk - D. K. Yadava; Ranjay K. Singh; V. B. Patel; T. R. Sharma; S. K. Singh; Sudhakar Pandey; P. R. Choudhury; Firoz Hossain; R. R. Burman; U. S. Gautam; Himanshu Pathak (Anthropocene Science, 2025)

In situ evaluation of genotoxicity and cytotoxicity associated with microplastics in an intertidal clam, Gafrarium divaricatum (Gmelin, 1791) - M. Harshavarthini; Shubra Singh; Prem Kumar; Martin Xavier; Saurav Kumar; Nalini Poojary; Madhuri S. Pathak; Kiran D. Rasal; Gajanan S. Ghode; Naresh S. Nagpure (Marine Pollution Bulletin, 2025)

Detection of elevated CO₂ and CH₄ emissions from power plant and landfill sites using airborne and spaceborne imaging spectroscopy - Hasmukh K. Varchand; Mehul R. Pandya; Jalpesh A. Dave; Parthkumar N. Parmar; Dhruv D. Desai; Manoj Singh; Dhiraj B. Shah; Vishal N. Pathak; Himanshu J. Trivedi (Atmospheric Pollution Research, 2025)

An economical and rapid method of comet assay and micronucleus cytome assay for genotoxicity biomonitoring using clam, Gafrarium divaricatum (Gmelin, 1791) - M. Harshavarthini; Edward Inpent Campal; Shubra Singh; Nalini Poojary; Martin Xavier; Kiran D. Rasal; Madhuri S. Pathak; Naresh S. Nagpure (DNA Repair, 2025)

Integration of Bioproducts with NPK for Improving Physiological Efficiency of Sugarcane and Sustaining Soil Quality Parameters in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak; Asha Gaur; Abhay Srivastava; Rishi Kumar; Mamta Chaoudhary (Sugar Tech, 2025)

Field-scale Estimation of Phenotypic Parameters for Jute and Allied Fibre Crops: An Unmanned Aerial Vehicle Remote Sensing Approach - Prabir Kumar Das; Tanumi Kumar; Dhananjay Barman; Mritunjay Kar; Sivaprasad Chunduri; Kunal Mandal; Debashish Dash; J. Nalini; D. Chamundeswari; Sabyasachi Mitra; Suparn Pathak; Gouranga Kar; et al. (Journal of the Indian Society of Remote Sensing, 2025)

Integration of Mycorrhizae, Azotobacter and Pseudomonas spp (PSB) with NPK and their Effects on Sugarcane Crop and Soil Health in Uttar Pradesh, India - M. K. Tripathi; S. K. Shukla; V. P. Jaiswal; Lalan Sharma; Mona Nagargade; A. D. Pathak; A. P. Dwivedi; Ankur Tripathi; V. K. Singh; V. P. Singh; Ajay Ranka (Sugar Tech, 2025)

Modified emission and scaling factors for methane and nitrous oxide in rice system of India: A country specific disaggregate approach - Pratap Bhattacharyya; A. Bhatia; N. Jain; D. Chatterjee; S. Mohanty; M. Prabhakar; Pratibha M; N.N. Jambhulkar; S. Ananthakrishnan; S.K. Nayak; A.K. Nayak; H. Pathak (Journal of Environmental Management, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A hybrid physics-based method for estimating land surface temperature using radiative transfer simulations and machine learning model from Sentinel-3A SLSTR observations - Jalpesh A. Dave; Vedant Pandya; Frank-M. Goettsche; Hasmukh K. Varchand; Parthkumar N. Parmar; Dhruv D. Desai; Disha B. Kardani; Dhiraj B. Shah; Ashwin Gujrati; Vishal N. Pathak; Himanshu J. Trivedi; Mehul R. Pandya (Earth Science Informatics, 2025)

Genomic Insights of Multidrug-Resistant Enterococcus faecalis and Acinetobacter baumannii Isolated from a Sepsis Patient with Pauci-Immune Crescentic Glomerulonephritis, India - Ujjayni B. Saha; Kunal K. Dixit; Savita V. Jadhav; Ketaki N. Pathak; Neetu S. Gupta; Sunil D. Saroj (Current Microbiology, 2025)

Phase dynamics of MJO and their correlation with Indian summer monsoon onsets - Riddhi D. Prajapati; Kamlesh N. Pathak; Niket Shastri (Theoretical and Applied Climatology, 2024)

Genetic Profiling of Spodoptera litura (Noctuidae: Lepidoptera) in Indian Sub-Tropical Sugar Beet - Santeshwari Srivastava; Varucha Misra; Arun Baitha; Himanshu Pandey; S. N. Sushil; M. Mohan; A. D. Pathak; Sangeeta Srivastava; Dinesh Singh; Ashutosh Kumar Mall (Sugar Tech, 2024)

Phenome-wide genetic-correlation analysis and genetically informed causal inference of amyotrophic lateral sclerosis - Salvatore D’Antona; Gita A. Pathak; Dora Koller; Danilo Porro; Claudia Cava; Renato Polimanti (Human Genetics, 2023)
Leveraging genome-wide association statistics generated from a large study of amyotrophic lateral sclerosis (ALS; 29,612 cases and 122,656 controls) and UK Biobank (UKB; 4,024 phenotypes, up to 361,194 participants), we conducted a phenome-wide analysis of ALS genetic liability and identified 46 genetically correlated traits, such as fluid intelligence score ( r g = − 0.21, p = 1.74 × 10 –6 ), "spending time in pub or social club” ( r g = 0.24, p = 2.77 × 10 –6 ), non-work related walking ( r g = − 0.25, p = 1.95 × 10 –6 ), college education ( r g = − 0.15, p = 7.08 × 10 –5 ), “ever diagnosed with panic attacks ( r g = 0.39, p = 4.24 × 10 –5 ), and “self-reported other gastritis including duodenitis” ( r g = 0.28, p = 1.4 × 10 –3 ). To assess the putative directionality of these genetic correlations, we conducted a latent causal variable analysis, identifying significant genetic causality proportions (gĉp) linking ALS genetic liability to seven traits. While the genetic component of “self-reported other gastritis including duodenitis" showed a causal effect on ALS (gĉp = 0.50, p = 1.26 × 10 –29 ), the genetic liability to ALS is potentially causal for multiple traits, also including an effect on "ever being diagnosed with panic attacks” (gĉp = 0.79, p = 5.011 × 10 –15 ) and inverse effects on “other leisure/social group activities” (gĉp = 0.66, p = 1 × 10 –4 ) and prospective memory result (gĉp = 0.35, p = 0.005). Our subsequent Mendelian randomization analysis indicated that some of these associations may be due to bidirectional effects. In conclusion, this phenome-wide investigation of ALS polygenic architecture highlights the widespread pleiotropy linking this disorder with several health domains.

Scoping the Need of Mainstreaming Indigenous Knowledge for Sustainable Use of Bioresources in the Indian Himalayan Region - Vikram S. Negi; Ravi Pathak; Shinny Thakur; Ravindra K. Joshi; Indra D. Bhatt; Ranbeer S. Rawal (Environmental Management, 2023)

Enhancing Crop Productivity and Profitability of Autumn Sugarcane with Intercropping of Winter Vegetables in Real Farming Situations of North-Central India - S. N. Singh; Chandra Gupta; V. K. Singh; A. D. Pathak; A. K. Sah; M. K. Tripathi; Sanjiv Gupta; J. R. Patnaik (Sugar Tech, 2023)

Efficient removal of total arsenic (As3+/5+) from contaminated water by novel strategies mediated iron and plant extract activated waste flowers of marigold - Sudhir K. Upadhyay; Priyanka Devi; Vinay Kumar; Himanshu K. Pathak; Prasann Kumar; Vishnu D. Rajput; Padmanabh Dwivedi (Chemosphere, 2023)

In vitro propagation and phytochemical analysis of Vanda cristata Wall. ex Lindl.: An endangered medicinal orchid of biopharmaceutical importance - Promila Pathak; Anamika Kumari; Brent D. Chandler; Lawrence W. Zettler (South African Journal of Botany, 2023)

Crop Residue Recycling Affecting Carbon Sequestration, Nutrients Availability and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat System - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak (Sugar Tech, 2023)

Adsorption of congo red using carbon from leaves and stem of water hyacinth: equilibrium, kinetics, thermodynamic studies - A. Extross; A. Waknis; C. Tagad; V. V. Gedam; P. D. Pathak (International Journal of Environmental Science and Technology, 2023)

Water and wastewater quality prediction: current trends and challenges in the implementation of artificial neural network - Anuja R. Jadhav; Pranav D. Pathak; Roshani Y. Raut (Environmental Monitoring and Assessment, 2023)

Breeding for Drought Tolerance in Sugarcane: Indian Perspective - A. K. Mall; Varucha Misra; A. D. Pathak; Sangeeta Srivastava (Sugar Tech, 2022)

Plant Quarantine Regulations With Reference to Sugarcane in India: Strengths and Challenges - S. N. Sushil; Deeksha Joshi; Sharmila Roy; G. P. Rao; A. D. Pathak (Sugar Tech, 2022)

Functionality of fructosphere bacteria Kocuria sediminis strain AC3 in plant growth promotion and biodegradation of the acephate in grape berries - Yogita H. Ranade; Sujoy Saha; Madhura Chandrashekar; Indu Sanjay Sawant; Raviraj C. Shinde; Pranav D. Pathak (Biologia, 2022)

Diversification Options in Sugarcane-Based Cropping Systems for Doubling Farmers’ Income in Subtropical India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. P. Dwivedi; S. K. Yadav; A. D. Pathak (Sugar Tech, 2022)

Potential of Bacillus altitudinis KMS-6 as a biocontrol agent of Meloidogyne javanica - Sonam Antil; Rakesh Kumar; D. V. Pathak; Anil Kumar; Anil Panwar; Anju Kumari; Vinod Kumar (Journal of Pest Science, 2022)

Fungitoxicity profile of Cladosporium cladosporioides C1, as a leveraging tool for postharvest management of grapes - Yogita H. Ranade; Pranav D. Pathak; Madhura Chandrashekar; Sujoy Saha (Biologia, 2022)

Climate risk insurance in Pacific Small Island Developing States: possibilities, challenges and vulnerabilities—a comprehensive review - Devendra Kumar Jain; Asif Chida; R. D. Pathak; Raghbendra Jha; Stephanie Russell (Mitigation and Adaptation Strategies for Global Change, 2022)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Sugar Beet Cultivation in India: Prospects for Bio-Ethanol Production and Value-Added Co-Products - Ashutosh Kumar Mall; Varucha Misra; Santeshwari; A. D. Pathak; Sangeeta Srivastava (Sugar Tech, 2021)

Management of Termites Through Different Tools and Their Impact on Environment and Soil Micro-arthropods in Sugarcane in Indo-Gangetic Plains of India - S. N. Sushil; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Identification of Appropriate Agri-technologies Minimizing Yield Gaps in Different Sugarcane-Growing States of India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; S. K. Awasthi; Adil Zubair; S. K. Yadav (Sugar Tech, 2021)

Effect of Long-Term Organic Fertilization in Flooded Rice Soil on Phosphorus Transformation and Phosphate Solubilizing Microorganisms - Dibyendu Chatterjee; A. K. Nayak; Annapurna Mishra; C. K. Swain; U. Kumar; D. Bhaduri; P. Panneerselvam; B. Lal; P. Gautam; H. Pathak (Journal of Soil Science and Plant Nutrition, 2021)

Potassium Influencing Physiological Parameters, Photosynthesis and Sugarcane Yield in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; Ishwar Singh; A. D. Pathak; Mona Nagargade; Arup Ghosh; C. Gupta; Asha Gaur; S. K. Awasthi; Raghvendra Tiwari; Abhay Srivastava; et al. (Sugar Tech, 2021)

Incidence and Diversity of Termites Associated with Sugarcane in North-West Zone of India with New Records - S. N. Sushil; C. M. Kalleshwaraswamy; M. Ranjith; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Sugarcane Yield Using Minimum Tillage Technology Through Subsoiling: Beneficial Impact on Soil Compaction, Carbon Conservation and Activity of Soil Enzymes - S. K. Shukla; V. P. Jaiswal; Lalan Sharma; A. D. Pathak; Akhilesh Kumar Singh; Rajendra Gupta; S. K. Awasthi; Asha Gaur; Adil Zubair; Raghvendra Tiwari (Sugar Tech, 2020)

Determination of Morphological and Biochemical Basis of Resistance Against Top Borer, Scirpophaga excerptalis Walker in Sugarcane - S. N. Sushil; Amaresh Chandra; Sharmila Roy; A. K. Jaiswal; M. R. Singh; A. D. Pathak (Sugar Tech, 2020)

Process of fruit peel waste biorefinery: a case study of citrus waste biorefinery, its environmental impacts and recommendations - Saurabh N. Joglekar; Pranav D. Pathak; Sachin A. Mandavgane; Bhaskar D. Kulkarni (Environmental Science and Pollution Research, 2019)

Alien plant invasion in the Indian Himalayan Region: state of knowledge and research priorities - Ravi Pathak; Vikram S. Negi; Ranbeer S. Rawal; Indra D. Bhatt (Biodiversity and Conservation, 2019)

In vivo high-resolution diffusion tensor imaging of the developing neonatal rat cortex and its relationship to glial and dendritic maturation - Markus Breu; Dominik Reisinger; Liangcheng Tao; Dan Wu; Yajing Zhang; Matthew D. Budde; Ali Fatemi; Arvind P. Pathak; Jiangyang Zhang (Brain Structure and Function, 2019)

Green Technologies for Improving Cane Sugar Productivity and Sustaining Soil Fertility in Sugarcane-Based Cropping System - S. K. Shukla; S. Solomon; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; Priyanka Singh (Sugar Tech, 2019)

Interplay of phosphorus doses, cyanobacterial inoculation, and elevated carbon dioxide on yield and phosphorus dynamics in cowpea - Sumit Kumar Dey; B. Chakrabarti; T. J. Purakayastha; Radha Prasanna; R. Mittal; S. D. Singh; H. Pathak (Environmental Monitoring and Assessment, 2019)

RuBisCo activase—a catalytic chaperone involved in modulating the RuBisCo activity and heat stress-tolerance in wheat - Ranjeet Ranjan Kumar; Suneha Goswami; Kavita Dubey; Khushboo Singh; Jyoti P. Singh; Ashok Kumar; Gyanendra Kumar Rai; Shiv Dhar Singh; Suman Bakshi; Bhupinder Singh; Himanshu Pathak; Viswanathan Chinnusamy; et al. (Journal of Plant Biochemistry and Biotechnology, 2019)

Ecosystem services in different agro-climatic zones in eastern India: impact of land use and land cover change - Rahul Tripathi; K. C. Moharana; A. D. Nayak; B. Dhal; Md Shahid; B. Mondal; S. D. Mohapatra; P. Bhattacharyya; Nuala Fitton; Pete Smith; A. K. Shukla; H. Pathak; et al. (Environmental Monitoring and Assessment, 2019)

Impact of seasonal thermal stress on physiological and blood biochemical parameters in pigs under different dietary energy levels - P. K. Pathak; R. Roychoudhury; J. Saharia; M. C. Borah; D. J. Dutta; R. Bhuyan; D. Kalita (Tropical Animal Health and Production, 2018)

Soil microbial responses as influenced by Jatropha plantation under rainfed condition in north-west India - Ahmad Mahmoud; S. D. Singh; K. S. Muralikrishna; H. Pathak; Namita Das Saha (Agroforestry Systems, 2018)

Identifying Seasonal Opportunities to Save Water: Using Weekly Rainfall and Evapotranspiration Patterns to Evaluate Outdoor Water Restriction Policy in South Florida - Felicia D. Survis; Tara L. Root; Chandra S. Pathak (Water Conservation Science and Engineering, 2017)

Soil Carbon Sequestration and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat Cropping Systems Through Crop Residue Management and Inoculation of Trichoderma viride in Subtropical India - S. K. Shukla; Swaha Shee; S. K. Maity; S. Solomon; S. K. Awasthi; Asha Gaur; A. D. Pathak; V. P. Jaiswal (Sugar Tech, 2017)

Crop Diversification Options Involving Pulses and Sugarcane for Improving Crop Productivity, Nutritional Security and Sustainability in India - S. K. Shukla; K. K. Singh; A. D. Pathak; V. P. Jaiswal; S. Solomon (Sugar Tech, 2017)

Habitat Fingerprinting Using Otolith Trace Metal Profile of Two Catfish Species of Genus Ompok (Siluridae) from Ganges Basin, India - U. K. Sarkar; A. K. Pathak; B. K. Gupta; D. D. Patra (Proceedings of the Zoological Society, 2016)

Influence of varying nitrogen levels on lipid accumulation in Chlorella sp. - B. Kiran; K. Pathak; R. Kumar; D. Deshmukh; N. Rani (International Journal of Environmental Science and Technology, 2016)

Effect of Sowing Date and Cultivars on Aphid Infestation in Wheat with Climate Change Adaptation Perspective - Subhash Chander; Mazhar Husain; Vishwa Pal; Himanshu Pathak; S. D. Singh; Ramesh Harit; Vinod Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Super-Optimal NPK Along with Foliar Iron Application Influences Bioavailability of Iron and Zinc of Wheat - Rajiv Rakshit; A. K. Patra; T. J. Purakayastha; R. D. Singh; H. Pathak; Shiva Dhar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

The Stress of Suicide: Temporal and Spatial Expression of Putative Heat Shock Protein 70 Protect the Cells from Heat Injury in Wheat (Triticum aestivum) - Ranjeet R. Kumar; Suneha Goswami; Richa Gupta; Pooja Verma; Khushboo Singh; Jyoti P. Singh; Mahesh Kumar; Sushil K. Sharma; Himanshu Pathak; Raj D. Rai (Journal of Plant Growth Regulation, 2016)

Cysteine-rich secretory protein 3 plays a role in prostate cancer cell invasion and affects expression of PSA and ANXA1 - Bhakti R. Pathak; Ananya A. Breed; Snehal Apte; Kshitish Acharya; Smita D. Mahale (Molecular and Cellular Biochemistry, 2016)

Calcium triggers protein kinases-induced signal transduction for augmenting the thermotolerance of developing wheat (Triticum aestivum) grain under the heat stress - Suneha Goswami; Ranjeet R. Kumar; Sushil K. Sharma; Yugal K. Kala; Khushboo Singh; Richa Gupta; Gaurav Dhavan; Gyanendra K. Rai; Gyanendra P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2015)

Salicylic acid alleviates the heat stress-induced oxidative damage of starch biosynthesis pathway by modulating the expression of heat-stable genes and proteins in wheat (Triticum aestivum) - Ranjeet R. Kumar; Sushil K. Sharma; Suneha Goswami; Pooja Verma; Khushboo Singh; Nidhi Dixit; Himanshu Pathak; C. Viswanathan; Raj D. Rai (Acta Physiologiae Plantarum, 2015)

Fecal lactoferrin and intestinal permeability are effective non-invasive markers in the diagnostic work-up of chronic diarrhea - Roberta Caccaro; Renata D’Incà; Matteo Martinato; Elisabetta Dal Pont; Surajit Pathak; Anna Chiara Frigo; Giacomo Carlo Sturniolo (BioMetals, 2014)

Ascorbic acid at pre-anthesis modulate the thermotolerance level of wheat (Triticum aestivum) pollen under heat stress - Ranjeet R. Kumar; Suneha Goswami; Kritika A. Gadpayle; Khushboo Singh; Sushil K. Sharma; G. P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2014)

Mitigation of greenhouse gas emission with system of rice intensification in the Indo-Gangetic Plains - Niveta Jain; Rachana Dubey; D. S. Dubey; Jagpal Singh; M. Khanna; H. Pathak; Arti Bhatia (Paddy and Water Environment, 2014)

Sugar Beet: A Historical Perspective in Indian Context - A. D. Pathak; Raman Kapur; S. Solomon; Rajesh Kumar; Sangeeta Srivastava; P. R. Singh (Sugar Tech, 2014)

Chemometric characterization of river water quality - Menka Kumari; Smriti Tripathi; Vinita Pathak; B. D. Tripathi (Environmental Monitoring and Assessment, 2013)

Differential expression of heat shock protein and alteration in osmolyte accumulation under heat stress in wheat - Ranjeet R. Kumar; Suneha Goswami; Sushil K. Sharma; Khushboo Singh; Kritika A. Gadpayle; S. D. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2013)

Dry direct-seeding of rice for mitigating greenhouse gas emission: field experimentation and simulation - H. Pathak; S. Sankhyan; D. S. Dubey; A. Bhatia; N. Jain (Paddy and Water Environment, 2013)

Supplementation of zinc mitigates the altered uptake and turnover of 65Zn in liver and whole body of diabetic rats - Ashima Pathak; Vishawjyoti Sharma; Sanjeev Kumar; D. K. Dhawan (BioMetals, 2011)

Altered phosphorylation and distribution status of vimentin in rat seminiferous epithelium following 17β-estradiol treatment - Rahul Upadhyay; Ryan D’Souza; Shobha Sonawane; Reshma Gaonkar; Shilpa Pathak; Aditi Jhadav; N. H. Balasinor (Histochemistry and Cell Biology, 2011)

Ameliorating effect of N-acetylcysteine and curcumin on pesticide-induced oxidative DNA damage in human peripheral blood mononuclear cells - Tanzeel Ahmed; Rahul Pathak; MD. Mustafa; Rajarshi Kar; Ashok K. Tripathi; Rafat S. Ahmed; B. D. Banerjee (Environmental Monitoring and Assessment, 2011)

Effect of Zinc Supplementation on the Status of Thyroid Hormones and Na, K, and Ca Levels in Blood Following Ethanol Feeding - R. Pathak; D. Dhawan; A. Pathak (Biological Trace Element Research, 2011)

Maternal and cord blood levels of Aldrin and Dieldrin in Delhi population - MD. Mustafa; Rahul Pathak; A. K. Tripathi; Rafat S. Ahmed; Kiran Guleria; B. D. Banerjee (Environmental Monitoring and Assessment, 2010)

Characterization of 2T engine oil degrading indigenous bacteria, isolated from high altitude (Mussoorie), India - Pankaj Kumar Jain; Vijai K. Gupta; Hardik Pathak; Madan Lowry; D. P. Jaroli (World Journal of Microbiology and Biotechnology, 2010)

Role of nodD gene product and flavonoid interactions in induction of nodulation genes in Mesorhizobium ciceri - D. V. Kamboj; Ranjana Bhatia; D. V. Pathak; P. K. Sharma (Physiology and Molecular Biology of Plants, 2010)

Site-specific nutrient management in rice in Eastern India using a modeling approach - D. K. Das; Debtanu Maiti; H. Pathak (Nutrient Cycling in Agroecosystems, 2009)

Distribution of vehicular pollutants in street canyons of Varanasi, India: a different case - Santosh K. Prajapati; B. D. Tripathi; Vinita Pathak (Environmental Monitoring and Assessment, 2009)

Reproductive pathways of seed development in apomictic guinea grass (Panicum maximum Jacq.) reveal uncoupling of apomixis components - P. Kaushal; D. R. Malaviya; A. K. Roy; Shalini Pathak; A. Agrawal; Ambica Khare; S. A. Siddiqui (Euphytica, 2008)

Dynamics of traffic noise in a tropical city Varanasi and its abatement through vegetation - Vinita Pathak; Brahma D. Tripathi; Virendra Kumar Mishra (Environmental Monitoring and Assessment, 2008)

Endosulfan and Other Organochlorine Pesticide Residues in Maternal and Cord Blood in North Indian Population - Rahul Pathak; Sanvidhan G. Suke; Rafat S. Ahmed; A. K. Tripathi; Kiran Guleria; C. S. Sharma; S. D. Makhijani; Meenu Mishra; B. D. Banerjee (Bulletin of Environmental Contamination and Toxicology, 2008)

Phytoremediation of Mercury and Arsenic from Tropical Opencast Coalmine Effluent Through Naturally Occurring Aquatic Macrophytes - Virendra Kumar Mishra; Alka Rani Upadhyay; Vinita Pathak; B. D. Tripathi (Water, Air, & Soil Pollution, 2008)

Stochastic Modeling of Progressive Failure in Heterogeneous Soil Slope - D. R. Pathak; H. N. Gharti; A. B. Singh; A. Hiratsuka (Geotechnical and Geological Engineering, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Isolation and characterization of mutants of Pseudomonas maltophila PM-4 altered in chitinolytic activity and antagonistic activity against root rot pathogens of clusterbean (Cyamopsis tetragonoloba) - E. Yadav; D. V. Pathak; S. K. Sharma; M. Kumar; P. K. Sharma (Indian Journal of Microbiology, 2007)

Use of Flyash and Biogas Slurry for Improving Wheat Yield and Physical Properties of Soil - R. N. Garg; H. Pathak; D. K. Das; R. K. Tomar (Environmental Monitoring and Assessment, 2005)

Major Indian expeditions ofSaccharum complex - A. D. Pathak; H. M. Srivastava; N. Kulshreshtha (Sugar Tech, 2003)

The role of potassium in sustaining yields in a long-term rice-wheat experiment in the Indo-Gangetic Plains of Nepal - Regmi A.; Ladha J.; Pasuquin E.; Pathak H.; Hobbs P.; Shrestha L.; Gharti D.; Duveiller E. (Biology and Fertility of Soils, 2002)

Heavy Metal Accumulation in Lichens from the Hetauda Industrial Area Narayani Zone Makwanpur District, Nepal - Vivek Pandey; D. K. Upreti; Ramayan Pathak; Amit Pal (Environmental Monitoring and Assessment, 2002)

Nitrous Oxide Emission from Soil with Different Fertilizers, Water Levels and Nitrification Inhibitors - H. Pathak; D. B. Nedwell (Water, Air, & Soil Pollution, 2001)

Long-term changes in yield and soil fertility in a twenty-year rice-wheat experiment in Nepal - Gami S.; Ladha J.; Pathak H.; Shah M.; Pasuquin E.; Pandey S.; Hobbs P.; Joshy D.; Mishra R. (Biology and Fertility of Soils, 2001)

Mitigation of N 2 O emission from an alluvial soil by application of karanjin - Majumdar D.; Dutta A.; Kumar S.; Pathak H.; Jain M. (Biology and Fertility of Soils, 2001)

Nitrous oxide emission from different fertilizers and its mitigation by nitrification inhibitors in irrigated rice - U. Kumar; M. C. Jain; H. Pathak; S. Kumar; D. Majumdar (Biology and Fertility of Soils, 2000)

Thyroid functions in lithium-treated psychiatric patients - S. D. Deodhar; B. Singh; C. M. Pathak; P. Sharan; P. Kulhara (Biological Trace Element Research, 1999)

Relationship between sugar maple decline and corresponding chemical changes in the stem tissue - H. K. Mohamed; S. Pathak; D. N. Roy; T. C. Hutchinson; D. L. McLaughlin; J. C. Kinch (Water, Air, & Soil Pollution, 1997)

RELATIONSHIP BETWEEN SUGAR MAPLE DECLINE AND CORRESPONDING CHEMICAL CHANGES IN THE STEM TISSUE - H. K. MOHAMED; S. PATHAK; D. N. ROY; T. C. HUTCHINSON; D. L. MCLAUGHLIN; J. C. KINCH (Water, Air, & Soil Pollution, 1997)

The Imperata grasslands of tropical Asia: area, distribution, and typology - D. P. Garrity; M. Soekardi; M. van Noordwijk; R. de la Cruz; P. S. Pathak; H. P. M. Gunasena; N. van So; G. Huijun; N. M. Majid (Agroforestry Systems, 1996)